The glass castle [videorecording (DVD)] - Cretton, Destin Daniel; Larson, Brie, 1989-; Harrelson, Woody; Watts, Naomi, 1968-; Walls, Jeannette (Lions Gate Entertainment, 2017)
Chronicling the adventures of an eccentric, resilient and tight-knit family. A remarkable story of unconditional love. A young woman who, influenced by the joyfully wild nature of her deeply dysfunctional father, found the fiery determination to carve out a successful life on her own terms.